Archives délaissées, archives retrouvées, archives explorées : les fonds calédoniens pour l’étude du patrimoine kanak dispersé - Marion Bertin (Les Cahiers de l'École du Louvre)
The Inventory of the Kanak scattered heritage (Inventaire du Patrimoine Kanak Dispersé, IPKD) and the « Objects as ambassadors » for Kanak culture are two projects with the same goal: to promote and improve knowledge on the ancient Kanak heritage located outside New Caledonia. These two projects were often quoted and commented on by the actors themselves and scholars, but the source material itself has stayed relatively unknown and un-consulted. Preserved by the museum of New Caledonia and by the cultural center Tjibaou in Noumea, these archives had never been considered until 2018. A research trip to New Caledonia for two and a half months gave us the opportunity to create an inventory and consult these archives. The diversity of the documents in the collection makes them a particularly interesting and valuable resource for researchers, and they elucidate the philosophy, timeline, and administrative organisation of the projects. This paper will present the two collections of archives and will focus on the documents themselves, rather than the results of their study.